Growth inhibition and induction of programmed cell death in the root of Helianthus annuus L. triggered by nickel ions and nickel-histidine complexes - Mackievic, Viera S.; Shyker, Artur A.; Zvanarou, Siarhej M.; Litskevich, Kiryl S.; Turovets, Oksana A.; Smolich, Ihar I.; Sokolik, Anatoly I.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2020)
Nickel (Ni2+) performs a number of vital functions in plants, but at high concentrations it causes toxic effects and inhibits their growth and development. The problem of nickel contamination has a special place in environmental physiology, since the refuse to use nickel alloys and therefore the reduction of Ni2+ release into the biosphere are practically impossible today. In nature one of the mechanisms of adaptation to the excessive nickel content in the medium is increased synthesis of histidine, which forms chelates with Ni2+. In the present work, for the first time, a detailed analysis of the effects of nickel and nickel-histidine complexes on the growth and development of sunflower roots (Helianthus annuus L.) of Belarusian selection (variety Orion) was carried out. It was established that Ni2+, starting from its level in the medium of 0.3 mmol/L, caused a significant growth inhibition of this agricultural plant. At a nickel concentration in the medium above 3 mmol/L, the growth of sunflower stopped completely. Histidine, introduced together with Ni2+, caused a decrease in the toxicity of this metal for the root system, in some cases shifting by single-order nickel concentrations, causing the same effect. Nickel treatment caused a significant increase in the percentage of cells with programmed cell death symptoms, while histidine inhibited the development of these symptoms. Thus, the concentration dependences of nickel and nickel-histidine complexes effects on root growth and the processes of programmed cell death in the sunflower root were first demonstrated.